UJI DAYA HAMBAT EKSTRAK AKAR TUMBUHAN Harrisonia perforata (Blanco) Merr. TERHADAP PERTUMBUHAN BAKTERI Staphylococcus epidermidis DAN Escherichia coli - Andi Aldi Matoro Putra; Orryani Lambui; Ramadhanil pitopang (Biocelebes, 2016)
Research of inhibition test from roots extract of Harrisonia perforata (Blanco) Merr. against to the growth of Staphylococcus epidermidis and Eschericia coli had been conducted during period of February to March 2015. The aim of this research was to gain the effectivity of roots extract to inhibited the growth of Staphylococcus epidermidis dan Escherichia coli. Reflux method used as the extraction method and Agar Diffusion method. The research was design by Completely Randomize Design (CRD) with 6 treatments and 3 replication. The treatments were roots extract concentrates 5%, 15%, 45% and 75%, positive control  Amoxicillin Clav-Acid 2% and negative control Na-CMC 1%. The result showed that roots extract of Harrisonia perforata (Blanco) Merr. had inhibition effect to the growth of bacterias. The extract concentrate 75% produced the biggest inhibition zone for both Staphylococcus epidermidis and Escherichia coli 17,46 mm and 26,33 mm. This shows that the roots extract of Harrisonia perforata (Blanco) Merr. have inhibitory effect on Staphylococcus epidermidis and Esherichia coli.   Keywords: Roots extract of Harrisonia perforata (Blanco) Merr., Staphylococcus epidermidis, Eschericia coli.